THE USE OF GROUND BLAST FURNACE SLAG , CHROME SLAG AND CORN STEM ASH AS A COATING AGAINST THE CORROSION - Reshka, Klevis (European Scientific Journal, ESJ, 2014)
Metals having chemical and electrochemical reactions with their surroundings can go bad and become unusable. It’s called corrosion. Many metals , especially iron , undergo corrosion when exposed to air and water. 1/10 of all metallic materials produced every year becomes unusable and it’s not possible to recycle them. Loss caused by corrosion costs billion of dollars every year. This study presents the results of corrosion resistance of ground blast furnace slag (GBFC) , chrome slag (CS)and corn stem ash. (CSA) In this study GBFC , CS and CSA , produced as a result of some procedures , are mixed with pitch in different portions. The reason for mixing with pitch is to gain the adherence. Then the iron plates were coated with this mixture. Coated and uncoated plates were undergone corrosion in Na Cl solution (35g/L Na Cl ). Having kept in the solution for one mount , the coated and uncoated plates were taken out and dried. The plates were put into Na Cl solution with the help of electrodes and the potential differences were measured. Our aim to do so was to reduce the potential difference. If the potential difference reduces , the electric currency reduces , so the corrosion is reduced too. The potential difference of the uncoated iron plates was 0.501 volts. Of coated with pitch 0.301 and mixed up with our experiment materials was 0. So the corrosion was reduced totally. This means: Billions of dollars loss is prevented A profitable use of GBFC , which is environmentally harmful , can be made and the nature can be protected. An economical use of CS , which is thrown away can be gained Some profit can be gained from corn stems that are left to be rotten in the fields. If the substance we’ve produced is used all the fields that iron is used , such as buildings , ships , water pipes etc , billions of dollars can be saved.